PENGARUH VARIABEL MIKRO DAN MAKRO EKONOMI TERHADAP RETURN SAHAM - Andyani, Kadek Windi; Mustanda, I Ketut (E-Jurnal Manajemen; Vol 7 No 4 (2018), 2018)
ABSTRACT This study determine the significant effect of CR, DER, ROE, TATO, EPS, interest rate, inflation rate, and exchange rate to stock return.This research was conducted on food and beverage sector companies in Indonesia Stock Exchange (IDX) period 2012-2016. The type of data used is quantitative data sourced from the official website of Indonesia Stock Exchange (IDX) and Bank Indonesia (BI). The number of samples of 12 companies that meet the criteria of research by using purposive sampling method. Data collection use non-participant observation method to document in the form of company's annual financial statements, interest rate, inflation and exchange rate during period 2012-2016. Data analysis technique used is multiple linear regression analysis. Based on the analysis result found that CR and DER have negative and insignificant effect to stock return, ROE have positive and significant effect to stock return, TATO, EPS, and positive and insignificant effect on stock return, inflation and exchange rate have negative and significant effect against stock return.   Keywords: cr, der, roe, tato, eps, interest rate, inflation, exchange rate, stock return.